REVIEW ON UBIQUITOUS CLOUDS AND PERSONAL MOBILE NETWORKS - Manoharan, Samuel (IRO Journal on Sustainable Wireless Systems, 2019)
The cloud that frame the future of the computing has become more popular nowadays due to its numerous attractive benefits such as self-servicing, resource-pooling, elasticity, improved-scalability, resilience , and operational and migration flexibility. This server-client model with the pay per usage facility is described by the NIST as the enabling, on-demand, convenient-network access, with shared pool of computing resources that are provided swiftly with the minimal efforts of management and interactions. The paper gives a brief review on the continuous cloud computing services, explaining its ubiquity, and then proceeds with the usefulness of the cloud services in the personal mobile network, that could enable an enhancement in the performance of the personal mobile network in the future.
Keywords: Ubiquitous cloud; deploying models of cloud; services of cloud; cloud advantages; personal mobile networks